Horoskopy Mahometa i pierwszych kalifów w tradycji przypisywanej Stefanowi z Aleksandrii - Karczewski, Łukasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
This article presents a philological and historical analysis of an eighth-century Greek astrological treatise attributed to the Pseudo-Stephanus of Alexandria, focusing on the figure of Muhammad and his politicalreligious legacy. The treatise includes a horoscope of the Prophet and a prophetic vision of the fate of the Arabs and the decline of the Umayyad dynasty. The study explores the structure and language of the text, its reliance on Ptolemaic astrology, and its incorporation of cosmological, medical, and theological concepts derived from late-antique traditions. Particular attention is given to rhetorical features, the use of classical sources – such as Aristotle, Galen, Manilius, and Dorotheus of Sidon – and the ideological function of the work in the context of Christian-Muslim polemics during the iconoclastic period.